Framework for the estimation of safe wake separation distance between same-track multi-rotor UAS - Wang, John Chung-Hung (2021)
As the surface traffic in modern cities becomes more congested, people turn to the vertical dimension to accommodate the projected increase in urban population density. In order to facilitate the utilization of the urban airspace for passenger and cargo transportation, however, a safe and efficient method of managing these traffic is needed. Several UAS (Unmanned Aircraft System) Traffic Management (UTM) concept of operations have been proposed and studied by various research agencies around the world to address this need, though hard data needed to validate the safety assessment of said concepts is lacking. The current paper proposes a hybridComputational Fluid Dynamics (CFD)-Flight Dynamics simulationworkflow to analyze the necessity of wake-vortex based separation standard for multi-rotor air-vehicles within the UTM controlled airspace. This is accomplished through the usage of Virtual Blade Model (VBM) to simplify the simulation of near-field wake of the multi-rotor air-vehicle, which is mapped into the LES domain to generate the wake-field that the SIMULINK flight dynamics model would use to generate the wake-encounter response of a follower multi-rotor air-vehicle The outlined workflow could be used to estimate the attitude of the follower vehicle and the associate rate of change for a given encounter-pair at various separation distance, which could eventually contribute, along with other factors such as navigational uncertainties etc., to the establishment of required-sizing for safety “bubble” around an UAS. This safe-separation requirement would impact the safety assessment and the overall capacity of the UTM system.